ANALISIS PENGARUH SISTEM PAYLATER TERHADAP SIKAP KONSUMTIF MASYARAKAT DARI SUDUT PANDANG HUKUM EKONOMI SYARIAH - Andriati, Syarifah Lisa (Journal of Sharia Economics, 2024)
In this era, human life is heavily influenced by technology, especially in terms of business. The use of PayLater, which means "buy now, pay later," is one example of the use of advanced technology in the business world. With technological advances in the modern era, especially e-commerce payment systems, SpayLater is becoming increasingly popular. PayLater is a purchase method that allows payments to be made later in a given period of time. In Islamic law, this is called the sale of Istijrar. However, scholars argue that it is a violation of the sale system when the goods to be bought are unknown to the buyer and there are new buyers who want to buy the same goods and set the price after summing up all the prices to pay. In fact, SpayLater can be permitted if the price of the goods has been determined after both parties involved in the transaction prove that the price is consistent with and in accordance with Islamic rules. This research aims to find out how PayLater transactions are used and how Islamic law views such actions. The method used is qualitative descriptive research, in which the author uses library studies, i.e., scientific references from books, national and international journals, al-Qur'an and Hadiths, and fiqih books. Because of its ease of use, SpayLater can make people prefer to buy something, which in turn will encourage them to make online debts. Therefore, knowing the potential risks, customers should be wise in distinguishing between needs and desires.